Pengaruh Lendutan Akibat Variasi Spasi Tulangan Geser Pada Balok Beton Bertulang Dengan Metode Finite Element - Anggi Agusstiawan; Reni Suryanita; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
At the time of installation the distance between the shear reinforcement is not planned properly. This affects the serviceability of reinforced concrete blocks. This study aims to see the effect of the planned shear reinforcement which is not according to the initial plan. So, an analysis of the effect of shear reinforcement on deflection was carried out using the LUSAS Finite Element. The results of the LUSAS Finite Element analysis show that the BS2 beam model with a maximum load of 40.5 kN has decreased deflection by 33.53 % against the planning according to SNI 03-2847-2019 (BS1) which has a maximum load of 46.55 kN. Furthermore, for the BS3 model with a maximum load of 38.69 kN, the deflection decreased by 35,03 % from the planning according to SNI 03-2847-2019 (BS1) which had a maximum load of 46.55 kN. It can be concluded that the spacing of the shear reinforcement can affect the deflection of the beam. Keywords : Beam, Shear Reinforcement, Deflection, LUSAS